Managing workplace bullying experiences in nursing: the impact of the work environment. Issue 5 (29th July 2017) - Blackwood, Kate; Bentley, Tim; Catley, Bevan; Edwards, Margot
Abstract : To progress our understanding of good practice in the management of workplace bullying, the authors explored the influence of work environment factors on bullying intervention. Analysis of focus group data from public hospitals in New Zealand revealed factors at multiple levels in the work environment system that influenced intervention. Many of these factors have previously been identified as antecedents to bullying, suggesting that the work environment hypothesis can also be applied to the management of workplace bullying experiences.